Vagabond - Cornwell, Bernard 1944- (HarperCollins, 2002)
From internationally bestselling author Bernard Cornwell comes the eagerly anticipated sequel to The Archer's Tale, in his acclaimed Grail Quest series, in which a young archer sets out to avenge his family's honor on the battlefields of the Hundred Years' War and winds up on a quest for the Holy Grail. 1347: a year of war and unrest. England's army is fighting in France, and its absence encourages the Scots to invade the old enemy. Thomas of Hookton, sent back to England to follow an ancient trail that suggests his family once owned the Holy Grail, instead becomes embroiled in the savage fight when the Scots come to Durham. Out of the horror he finds a new companion for the quest but also discovers a new and sinister enemy in a Dominican Inquisitor. All Europe wants the grail. Many may doubt it even exists, but no one would willingly allow an enemy to find Christendom's most precious relic, and Thomas finds himself in a murderous race with the Inquisitor and with Guy de Vexille, the mysterious black rider who murdered Thomas's father (in The Archer's Tale). Thomas appears to have an advantage in the race. His father bequeathed him a mysterious notebook that confirms the grail's existence and offers clues to where the relic might be hidden. But his rivals, inspired by a fanatical religious fervor, have their own advantage-the torture chamber of the Inquisition. Thomas, seeking help to decipher the book's cryptic pages, is delivered instead to his worst enemies. He finds refuge in Brittany, with Jeanette, the Countess of Armorica, but fate will not let him rest. He is thrust into one of the bloodiest and most desperate fights of the Hundred Years' War, the Battle of la Roche-Derrien, and amid the flames, arrows, and butchery of that night, he faces his enemies again.